A preliminary report of clinical experience in managing patients with sepsis and septic shock in emergency medicine ward. Issue 1 (January 2019) - Li, Chun Kit; Wong, Oi Fung; Ko, Shing; Ma, Hing Man; Lit, Chau Hung Albert
Background: Sepsis and septic shock are common causes of hospital admission, morbidity, and mortality, posing a significant burden on the health-care systems. Objective: The objective of this study was to report the clinical experience of management and outcomes of sepsis patients in the emergency medical ward of a community hospital. The risk factors associated with adverse outcomes of sepsis patients were also analyzed. Methods: This was a retrospective cohort study of patients with sepsis or septic shock managed in the emergency medical ward of North Lantau Hospital from 1 March 2015 to 31 March 2017. Their characteristics, clinical outcomes, risk factors associated with in-hospital mortality, 28-day mortality, and prolonged hospital stay (>14 days) were analyzed. Results: A total of 68 eligible patients met the inclusion criteria during the study period. The mean age of the patients was 73 (standard deviation, 16.7; range, 34–100) years. The mean Sequential Organ Failure Assessment score of all the cases was 4.5 (standard deviation, 2.4); range, 2–11). The most common source of infection was pneumonia (50%). During the stay in the emergency medical ward, 35 cases (49%) required vasopressor support for management of septic shock, and 12 cases required non-invasive ventilation (NIV) support. Five patients were eventually transferred to tertiary hospital (Princess Margaret Hospital) for further management. There were five in-hospital mortality cases and two 28-day mortality cases. From the univariate analysis, factors associated with in-hospital mortality included Sequential Organ Failure Assessment score >6 (p < 0.000), increasing number of organ dysfunction (p < 0.000), presence of chronic liver disease (p = 0.025), respiratory dysfunction during admission (p = 0.028); factors associated with 28-day mortality were advanced age (p < 0.000), increasing number of organ dysfunction (p = 0.033), presence of congestive heart failure (p = 0.004), and the presence of cancer (p = 0.034); factors associated with prolonged hospital stay were advanced age, presence of chronic obstructive airway disease (p = 0.003), advanced age (p = 0.041), and the use of NIV support (p = 0.001). In multivariate analysis, weak associations between in-hospital mortality and Sequential Organ Failure Assessment score >6 (p = 0.226) and increased number of organ dysfunction (p = 0.108) were demonstrated; there was a trend of prolonged length of stay with increased age (p = 0.139). Conclusion: Our experience and knowledge in managing sepsis patients in the emergency medical ward with implementation of critical care bed services increased significantly. These preliminary results demonstrated that, with appropriate patient selection, sepsis patients can be safely managed in the emergency medical ward. Further study with larger sample size is needed to identify risk factors of adverse outcomes in this group of patients managed in the emergency medical ward.